Strategi Penguatan Stimulasi Psikososial melalui Pelatihan Pijat Bayi: Upaya Holistik Percepatan Penurunan Stunting di Desa Kaenbaun, Kabupaten Timor Tengah Utara - Naibaho, Flora; Simbolon, Romida; Sepeh, Yandri Ratu (Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting is a chronic nutritional problem that affects children’s physical growth, cognitive development, and long-term health. Efforts to reduce stunting should not only focus on nutritional fulfillment but also require a holistic approach that includes psychosocial aspects. This study/community service aims to introduce and implement infant massage training as a psychosocial intervention to support the acceleration of stunting reduction in Kainbaun Village, Timor Tengah Utara Regency.The methods of the activity include socialization with mothers and families regarding the benefist of infant massage, demonstrations of proper massage practices, and continuous assistance to ensure that the skills can be applied independently. Infant massage has been proven to help improve sleep quality, increase appetite, strengthen the emotional bond between mother and child, and stimulate the nervous system and blood circulation. The results of the activity showed an increase in mothers’ knowledge and skills in performing infant massage, as well as positive changes in family psychosocial interactions. This, infant massage training can serve as a holistic strategy that integrates nutrition, health, and psychosocial aspects in efforts to accelerate stunting reduction in Kainbaun Village.